In2O3:Ga and In2O3:P-based one-electrode gas sensors: Comparative study. Issue 6 (July 2015) - Korotcenkov, G.; Boris, Iu.; Brinzari, V.; Han, S.H.; Cho, B.K.; Lychkovsky, Yu.N.
Abstract: Gas sensing characteristics of one-electrode sensors based on the In2 O3 ceramics doped by gallium and phosphorus have been discussed. In2 O3 -based ceramic was prepared by sol–gel technology. Ozone, CO, CH4 and H2 were used as tested gases. The doping concentration effect on the sensor parameters such as magnitude of response, operating temperature, response and recovery times, sensitivity to the air humidity, and selectivity have been analyzed. It was shown that In2 O3 doping by Ga and P could be used for the sensor performance optimization. It was assumed that the appearance of the second phase (InPO4 and Ga2 O3 ) and the change of structural parameters, taking place during doping process, were the main factors controlling the change of operating characteristics in In2 O3 :P and In2 O3 :Ga-based sensors.